What Is The Influence Of Compensation And Workload On Employee Performance - Kania Laelawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Previous research states that job satisfaction is one of the most complex areas that managers face today in terms of managing their employees (Komariyah, 2023). Some factors affecting employee satisfaction are workloads and compensation (Komariyah, 2022). Workload has a negative impact on job satisfaction, and compensation has a positive impact on work satisfaction and has a strong relationship. The research was conducted using descriptive and verification methods, and calculations were performed using the SPSS 20.0 program. Data collection was obtained through observations and questionnaires. Sampling is purposive random sampling. The respondents in this study were employees of a textile company in Subang City. The results of this study conclude that: 1) Compensation in the category is excellent. 2) The workload in the category is sufficient. 3) Job satisfaction in the good category has a significant impact on job satisfaction. Thus, it can be concluded that there is an influence of compensation and workload on job satisfaction.